Case review: Maritime New Zealand v A Gibson - Lill, Joseph (New Zealand Journal of Health and Safety Practice, 2025)
The criminal prosecution of Anthony Gibson, the former CEO of Port of Auckland Limited (POAL), involved various allegations of breaches of the due diligence obligation under the Health and Safety at Work Act 2015 (HSWA) with the charge being proven in the District Court. The case involved leading experts who commented on deficiencies in the health and safety system which ultimately contributed to Mr Gibson being found guilty.